Head teacher Leadership Styles and Teacher Performance in Primary Schools in Kaabong District, Uganda - Akullo, Elizabeth Akullo; Kamanyire, Venance Kamanyire (Journal of Education and Practice, 2023)
Purpose: This study investigated the influence of headteacher leadership styles on teacher performance in primary schools in Kaabong District. Specifically, the study was to establish whether headteacher transformational leadership style had a significant influence on teacher performance; whether headteacher instructional leadership style had a significant influence on teacher performance; and whether headteacher transactional leadership style had a significant influence on teacher performance in primary schools in Kaabong District. Methodology: The study adopted a cross-sectional descriptive survey research design in which structured questionnaires and face-to-face interviews were used to collect data from 308 respondents that included headteachers, directors of studies, teachers, pupil leaders and members of school management committees. The sampling of respondents was done mainly using simple random and census. Findings: The study found out that most headteachers in primary schools in Kaabong used the three leadership styles in their management. However, the study found out that most of the respondents disagreed that teacher performance in the primary schools was good. The results of the linear regression showed that use of transformational leadership style had an insignificant influence on teacher performance; use of instructional leadership style had a moderate significant influence on teacher performance; and use of transactional leadership style had an insignificant influence on the teacher performance in the primary schools. Unique Contribution to Theory, Policy and Practice: The findings of the study will provide a basis for policy makers to consider which leadership styles to emphasize in a bid to improve on teacher performance in schools. The findings from this study will provide an insight among head teachers on the importance of adopting appropriate leadership styles that can ensure good teacher performance in the primary schools. The findings will provide a basis for identifying the relationship between head teachers and teachers in forging best practices for improved teacher performance in schools.